2016
DOI: 10.1186/s12879-016-1745-2
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin resistance mutations in the 81 bp RRDR of rpoB gene in Mycobacterium tuberculosis clinical isolates using Xpert MTB/RIF in Khyber Pakhtunkhwa, Pakistan: a retrospective study

Abstract: BackgroundMulti-drug resistant tuberculosis (MDR-TB) is a major public health problem especially in developing countries. World Health Organization (WHO) recommends use of Xpert MTB/RIF assay to simultaneously detecting Mycobacterium tuberculosis (MTB) and rifampicin (RIF) resistance. The primary objective of this study was to determine the frequency of MDR-TB in patients suspected to have drug resistance in Khyber Pakhtunkhwa. The frequency of probes for various rpoB gene mutations using Xpert MTB/RIF assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
45
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 25 publications
11
45
1
Order By: Relevance
“…World health organization (WHO) endorsed Xpert® MTB/RIF assay for the diagnosis of Mycobacterium tuberculosis (MTB) and the mutations that confer Rifampicin resistance (RR) [1]. This assay has revolutionized the diagnosis of TB by simultaneously detecting the bacteria and RR [2,3], which is a surrogate marker for MDR-TB [2,4]. RR is determined based on mutations in the 81 bp (codons 507-533) regions of the β-subunit of the RNA polymerase enzyme (rpoB) gene using five overlapping probes [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…World health organization (WHO) endorsed Xpert® MTB/RIF assay for the diagnosis of Mycobacterium tuberculosis (MTB) and the mutations that confer Rifampicin resistance (RR) [1]. This assay has revolutionized the diagnosis of TB by simultaneously detecting the bacteria and RR [2,3], which is a surrogate marker for MDR-TB [2,4]. RR is determined based on mutations in the 81 bp (codons 507-533) regions of the β-subunit of the RNA polymerase enzyme (rpoB) gene using five overlapping probes [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…These probes are named as Probe A (codons 507-511), Probe B (codons 511-518), Probe C (codons 518-523), Probe D (codons 523-529) and Probe E (codons 529-533) [3,5]. A mutation in these regions accounts for more than 95% of RR [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence and spread of drug-resistant MTB strain largely associated with inadequate treatment. MDR-TB is caused by MTB that is resistant to at least two of the most powerful first-line anti-TB drugs, isoniazid (INH), and rifampicin (RIF) [3,4]. It was estimated that from 480,000 new cases of MDR-TB in the worldwide, about 9% of them were advanced to extensively drug-resistant TB (XDR-TB) and approximately 190, 000 were dead [2,[5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in Khyber Pakhtoonkhwa, Pakistan found that Probe E mutation was the most common rpoB genetic mutation (77%). 13 However, they also found less common mutations in Probe B (10.8%), D (8.3%), A (1.2%), and C (1.5%). Similarly, in China reported mutations were in codons 531 (41%), 526 (40%), and 513 (4%) in 81-bp.…”
Section: Discussionmentioning
confidence: 93%